Application of high‐pressure homogenization to improve physicochemical and antioxidant properties of almond hulls. (14th December 2022) - Liu, Juer; Huang, Li; An, Jun; Ma, Yiwei; Cheng, Yanling; Zhang, Renchuan; Peng, Peng; Wang, Yuanpu; Addy, Min; Chen, Paul; Chen, Chi; Liu, Yuhuan; et al.
Abstract: Almond hull contains a high level of dietary fiber and antioxidants, yet is under‐utilized, primarily as livestock feed. The present work aimed to evaluate the physiochemical and functional properties of almond hull powders, processed by high‐pressure homogenization (HPH), and any changes to their antioxidant properties after HPH treatment. It was found that the HPH treatment reduced the mean particle size and created a porous structure of the almond hull powders after lyophilization (freeze drying); hence, a significant increase ( p  < 0.05) in water holding capacity and oil holding capacity after processing, resulted in a much‐improved emulsifying capability. Additionally, based on their physical properties, the chosen variety (Carmel/Monterey) of almond hull extracts produced using the HPH process, showed the highest (1, 1‐diphenyl‐2‐picrylhydrazyl [DPPH]) radical‐scavenging capacity (119.11 ± 5.27 mg TE/g dw) and ferric reducing power (167.52 ± 10.55 mg TE/g dw, under 22, 000 psi = 152 MPa), along with the highest total flavonoid content (as 107.36 ± 3.76 mg QE/g dw). Overall, the high‐pressure homogenization process has effectively improved the physicochemical and functional properties of almond hull powder. Practical Applications: This green technology can effectively improve the water holding capacity, oil capacity, emulsifying capacity, as well as a potential process that can enhance the bioavailability and functionality of almond hull, and therefore this abundantly available byproduct can be converted to various value‐added ingredients and products such as emulsifier, clouding agent, nutritional supplement, and so on, in the huge interests of high‐quality, all‐natural, and healthy food market to date. Abstract :